Manifesto of the Communist Party – Reception and Criticism - Trkulja, Jovica D. (Sociološki pregled, 2018)
This paper aims to contribute to better understanding the reception and criticism of the Manifesto of the Communist Party through its turbulent history. Debates and controversies about its signifcance and topicality are raging still, since its very publication in 1848. Some have accepted it, praised it and seen it as the single best written political text and programme document relevant in today’s neoliberal globalization. The others have disputed and rejected it, since it was turned into a criminal ideology and practice that can be blamed for over 100 million deaths in the 20th century.The author of this text critically evaluates these two extreme points of view. First he assesses the impact of the Manifesto on social movements and political struggles since mid-19th century until the end of the 20th century, followed by the analyses of limitations and contradictions of some of Marx’s concepts from the Manifesto that led to a crisis and rejection of Marxism in late 20th century, as a conceptual and theoretic platform for the action of the working-class and other emancipation movements. In the conclusion, the author points out that the attitude towards the Manifesto has largely depended on the rise and fall of working-class and other emancipation movements in Europe and worldwide. The said work is still signifcant today for theoretical research and social and political reconsideration. Many of its concepts and formulations are outdated indeed, but their overall spirit has not lost its relevance, making the Manifesto of the Communist Party still an impetus for progressive powers in their struggle for more humanist world.Keywords: Karl Marx, Friedrich Engels, Manifesto of the Communist Party, working class movement, internationals, Marxism, socialism, social democracy, Eurocommunism, transition, globalization.